Economic principles for the hospitality industry - Siu, Ricardo Chi Sen (Hospitality essentials series, 2019)
"Economics Principles for the Hospitality Industry is the ideal introduction to the fundamentals of economics in this dynamic and highly competitive sector. Applying economic theory to a range of diverse and global hospitality industry settings, this book gives the theory real-world context. Looking at critical issues around sustainable economic development in the hospitality industry such as diversification, technology, determinates of demand, and pricing, it enables students to effectively conduct business analyses, evaluate business performance and conduct effective improvements over time. Written in an engaging style, this book assumes no prior knowledge of economics and contains a range of features, including international case studies and discussion questions, to aid beginners in the subject. This will be an essential introductory yet comprehensive resource on economics for all hospitality students"--